Wpływ skały macierzystej na produkcyjność lasów dębowych lasostepu lewobrzeżnej Ukrainy - Raspopina, Svitlana; Boiko, Sergii; Neyko, Ihor (Leśne Prace Badawcze, 2011)
The properties of parent material underlying the soil are important in the development of primary soil classifications and consequently affect stand productivity. This connection was studied in two stages: firstly through a general assessment of soil potencial for forest, and secondly, through determination of physical and chemical soil characteristics. The studies were conducted using those standard methods practiced in Ukraine, such as forest inventory, forest typology and soil analyses. Oak forests growing on sandy clayey soils were found to be more productive than those growing on the soils with a high clay fraction. The difference in stand productivity may be due to a five- to sevenfold reduction in the concentration of exchangeable cations of potassium (K + ) and calcium (Ca 2 + ) in the soil. While the proportion of calcium in the adsorption complex in highly-productive oak stands was 61 %, the proportion of this element in less-productive oak stands was only 17 %. A decrease in the productivity of stands of the I-II class bonitet (expressed in terms of the average height of a stand) is anticipated for those forest stands growing in soils overlying parent rock rich with magnesium (e.g. with a 80% proportion of magnesium). The least productive forest stands were growing on parent material characterised by a high proportion of magnesium Mg 2 + , fivefold lower share of Ca 2 + and sevenfold lower share of K + . The exchangeable cations in the soils of poorly-productive stands are characterised by 1:5 ratio of Ca/Mg ions. This ratio has a negative effect on calcium uptake by woody plants. The optimal ratio of Ca/ Mg ions in the soils for highly productive oak stands is 3:1.